Status of knowledge, attitude and practice of clinical nurses towards the intrahospital transport of critically ill patients: A cross‐sectional study - Jie Dong; Yayan Yi; Xiaocha Zhu; Huafang Zhang (Wiley, 2024)
Abstract Aims To explore the knowledge, attitudes and practice status of the intrahospital transport (IHT) of critically ill patients among clinical nurses and their influencing factors. Design Cross‐sectional study. Methods A questionnaire determined the nurses' knowledge, attitudes and practice scores. The questionnaire was used for data collection in a tertiary hospital from 10 January to 17 January 2023. Multivariate regression analysis was also used to evaluate the related factors of IHT of critically ill patients in different dimensions. Results Out of 670 distributed questionnaires, 612 nurses returned the completed questionnaire. The scores of KAP were (9.72 ± 1.61), (42.91 ± 4.58) and (82.84 ± 1.61), respectively. Pearson's correlation analysis showed that knowledge, attitude and behaviour scores were positively correlated. Variables that were associated with the scores of transfer knowledge were the scores of transfer practice, different departments and the scores of transfer attitude. The score of practice, number of IHT and received hospital‐level training had statistical significance on the nurses' attitude scores. Furthermore, the score of the attitude and transport knowledge had statistical significance on the nurses' practice. Conclusion The findings indicate a clear need for clinical nurses' knowledge of IHT of critically ill patients, especially in the emergency department (ED) and ICU. In addition, nurses need to be more active in transporting critically ill patients. Managers should enhance nurses' confidence in the IHT of critically ill patients and promote clinical nurses to establish a correct and positive attitude. Impact The findings of this study benefit nursing managers in understanding the current situation of IHT of critically ill patients. Managers should apply new training methods to nursing education and develop a multi‐level training program that is systematic, comprehensive and demand‐oriented. Patient or Public Contribution The participants of this study were nurses and this contribution has been explained in the Data collection section. There was no patient contribution in this study.